Retrospective analysis of 1,211 operated patients due to groin hernia with open surgical approach – single center experience - Marković, Miroslav; Bezmarevic, Mihailo; Ilić, Milan; Dragičević, Marina; Andrić, Aleksandar (Vojnosanitetski pregled, 2020)
Bacground/Aim. Groin hernias are common pathology among men population. Only curative treatment is surgical reparation with various surgical procedures for groin hernia solving. The aim of this study was to evaluate the most prevalent surgical procedures and early postoperative complications after groin hernia reparation in large series of operated patients, and to assess the morphologic characteristics of groin hernias. Methods. The retrospective study included all patients with groin hernia who underwent surgical reparation from 2009 to 2012. In all patients a demographic characteristics, including gender and age, clinical characteristics and hernia type were analyzed. The surgical procedure for hernia solving and early postoperative complications were assessed. Results. The study included 1,211 patients. The male/female ratio was 1,127/84 (p < 0.001). Inguinal hernia was found in 1,195 patients (94.5% males). Femoral hernia was found in 16 patients (25% males and 75% females). Significant difference in distribution of inguinal and femoral hernia between genders was found (p < 0.001). In males right sided inguinal hernia was present in 57.6%. In females right sided inguinal hernia was present in 7 and left sided in 5 patients. Sixsten patients had bilateral inguinal hernia, all in males. There was no significant difference in side of inguinal hernia occurrence and gender. Right sided and left sided femoral hernias were present in the same percent in males. In females a higher occurrence in femoral hernia was found on the right side then on the left one (7:5) without significant difference. There were 71.1% of patients in the age group of 51–80 and 27.2% of patients in the age group of 61–70. Surgical procedures included: Lichtenstein in 51.2% of patients, nylon-darn in 29.6% of patients, Bassini in 16.2% of patients, Lothaissen in 1.7% of patients, and Halsted in 1.4% of patients. Overall, postoperative complications were present in 78 (6.4%) of patients. Wound infection was the most common complication, occurred in 2.4% of patients. Conclusion. Prevalence of inguinal hernias is higher in men population, while femoral hernias are more common in females. The most affected population is at the age between 61 and 80 years. The most commonly used open surgical procedures for groin hernia reparation are Lichtenstein and nylon-darn. Both methods have low and similar incidence rates of postoperative complications.